A practical approach to neurophysiologic intraoperative monitoring - Husain, Aatif; Craig, R.; Davis, Aimee (New York : Demos, 2008)
This long-needed new book covers all critical aspects of neurophysiologic intraoperative monitoring, the procedure used to continuously assess.
1. Basic principles II. Clinical Methods
Incluye referencias bibliográficas e índice Título en inglés
Keywords: NEUROPHYSIOLOGIC - MONITORING; Monitoring, Intraoperative- methods